2000
DOI: 10.1016/s0735-1097(00)00517-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged recovery of cardiac output after maximal exercise in patients with chronic heart failure

Abstract: Prolonged kinetics of VO2 or VCO2 during recovery from maximal exercise represent impairment of circulatory response to exercise and delayed recovery of cardiac output after exercise. Overshoot of cardiac output at 1 min of recovery was characteristic of severe CHF with poor cardiac output response to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 35 publications
3
46
0
1
Order By: Relevance
“…ψ The SS is a marker of disease severity for the CF patients only. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 28 and is prolonged in adults with heart failure 29 when compared to controls 27 and COPD. 31 The metabolic cost of exercise results from both the performance of external work, and the demands of the oxygen transport system itself, including the work performed by the muscles for respiration and persistent hypermetabolism recognised during Assessing the rate at which the patient recovers from exercise may provide additional information on current health-status.…”
Section: Resultsmentioning
confidence: 99%
“…ψ The SS is a marker of disease severity for the CF patients only. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 28 and is prolonged in adults with heart failure 29 when compared to controls 27 and COPD. 31 The metabolic cost of exercise results from both the performance of external work, and the demands of the oxygen transport system itself, including the work performed by the muscles for respiration and persistent hypermetabolism recognised during Assessing the rate at which the patient recovers from exercise may provide additional information on current health-status.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with chronic heart failure, the time required for VO 2 to recover after exercise is prolonged, and the slower recovery is associated with the severity of the disease [3,17,18,37,38,39]. The prolonged recovery time in patients with chronic heart failure may be a result of the impaired ability of the cardiocirculatory system to rapidly deliver the amount of oxygen needed to fully replenish myoglobin in the peripheral muscles [3,40]. In addition, prolonged CO 2 output kinetics during recovery from exercise may also play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prolonged CO 2 output kinetics during recovery from exercise may also play a significant role. Tanabe et al [40] found that not only oxygen uptake during recovery from exercise was delayed, but also cardiac output fell much more slowly after maximal exercise. The delayed decrease in cardiac output during recovery in patients with chronic heart failure is predominantly responsible for CO 2 elimination [38,40].…”
Section: Discussionmentioning
confidence: 99%
“…4 The phenomenon was attributed to a sudden decrease in end-systolic volume. Tanabe et al 5 reported the overshoot of cardiac output during recovery after maximal exercise in approximately one-third of patients with chronic heart failure. The patients with overshoot of cardiac output had lower maximal cardiac output during exercise than the patients without overshoot.…”
mentioning
confidence: 99%
“…The patients with overshoot of cardiac output had lower maximal cardiac output during exercise than the patients without overshoot. 5 V O2 is equal to cardiac output × arterial -mixed venous O2 difference (C[a-v]O2). As such, an overshoot of cardiac output might result in an overshoot of V O2.…”
mentioning
confidence: 99%